2001
DOI: 10.1023/a:1011115207518
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of a weekly schedule of oxaliplatin, high-dose leucovorin, and infusional fluorouracil in pretreated patients with advanced colorectal cancer

Abstract: Our results show that L-OHP, LV and 5-FU can be administered safely and repetitively using a weekly schedule. Diarrhea and neutropenia are the DLT of this regimen. Its activity and its manageable toxicity profile deserve further evaluation in chemotherapy-naïve MCRC patients. The doses recommended for phase II trials are: L-OHP 65 mg/m2, LV 500 mg/m2 and 5-FU48h 2300 mg/m2 infusion given on a weekly-times-four schedule followed by a one-week rest period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
3
7
0
Order By: Relevance
“…We found evidence that our regimen decreases the specific drug neurotoxicity. Possible sources of reduced neurotoxicity include the weekly schedule developed by our group and confirmed by other studies with the same reduced toxicity [16,17,18]and a lower L-OHP dosage for single administration. Only 2 patients experienced grade 3 myelotoxicity.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We found evidence that our regimen decreases the specific drug neurotoxicity. Possible sources of reduced neurotoxicity include the weekly schedule developed by our group and confirmed by other studies with the same reduced toxicity [16,17,18]and a lower L-OHP dosage for single administration. Only 2 patients experienced grade 3 myelotoxicity.…”
Section: Discussionsupporting
confidence: 63%
“…After taking into account its reduced neurotoxicity in the weekly schedule [16,17,18],we preferred an L-OHP subdivision dosage at 65 mg/m 2 for single administration. The secondary aims were to evaluate the treatment in terms of time to disease progression (TTP), overall survival (OS), and QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the disease leads to the formation of plaques and lesions in various areas of the brain and the spinal cord. MS predominately affects people of temperate latitudes in the Western hemisphere, and its prevalence, depending on the different countries, ranges from 4 to 248 per 100,000 (1). About two million people worldwide suffer from MS, and it remains one of the leading causes of disability in young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Oxaliplatin is traditionally administered by a 2-hour infusion. However, it was demonstrated that a continuous infusion of oxaliplatin (4–12 h) is feasible, because pharmacokinetic profiles are similar to those profiles registered after chronomodulated infusion [20,21,22,23,24,25]. We decided to use continuous infusion of oxaliplatin with the aim to maximize the clinical efficacy infusing the drug during its higher cytotoxic efficacy hours.…”
Section: Introductionmentioning
confidence: 99%
“…We decided to use continuous infusion of oxaliplatin with the aim to maximize the clinical efficacy infusing the drug during its higher cytotoxic efficacy hours. Few studies demonstrated that the weekly administration of oxaliplatin is feasible with a high clinical efficacy and a good toxicity profile compared with the biweekly or three-weekly schedules [25,26,27]. …”
Section: Introductionmentioning
confidence: 99%